Privacy policy in Indonesia and Malaysia: from digital economy to personal data protection laws - Zulhuda, Sonny (2017)
Malaysia and Indonesia embrace the digital economy with a hope to emulate the success of other nations in making the ICT as the enabling infrastructure for development. Integral to that, the nations had also improved their legal and regulatory infrastructure to provide a conducive environment for the digital economy. Central to the legal infrastructure is the laws on personal data protection (PDP). Stemming from the preservation of the right to information privacy, the PDP law rose to become the next big thing in the international and regional trade and business too. Issues such as data cloud, data transfer and data security become increasingly a global concern that requires global and regional cooperation. With this background, this presentation is expected to highlight the latest development of the PDP laws in the two countries as triggered, In Malaysia, by the enactment of the Personal Data Protection Act 2010 (Act 709); and in Indonesia, by the amendment to the Law No. 11/2008 on Information and Electronic Transactions as well as the Ministerial Regulation No. 20/2016 on Personal Data Protection pertaining to the Electronic System. It is interesting to note that the two countries which seemed to initially have different concerns have finally come towards the same direction on the issue of personal data protection. The presentation will show the development in terms of enforcement, industrial involvement, as well as various rights of data subject relating to the personal information. At the end, the presentation calls for the need to have stronger and more intensive regional collaboration between legal fraternity, academia and regulators in addressing data protection issues. This is unavoidable because the threat we face is global.